The contribution of field trips to learning: Greek teachers’ beliefs - Evaggelia Zotou (International Journal of Educational Excellence and Innovation, 2025)
Although there have been numerous studies examining the impacts of fieldtrips, few studies have carefully examined Greek teacher’s perspective toward these experiences The aim of this study is to investigate Greek senior high-school teachers’ beliefs as far as the contribution of field trips to experiential learning is concerned and analyze their impact on student development. This study uses qualitative methods with semi-structured interviews of 20 teachers. The findings suggest that teachers view field trips as an important learning experience that facilitate and improve knowledge. The study concludes that field trips positively affect learning, empathy and critical thinking skills.